DISPARITAS KEWENANGAN PENJUALAN OBJEK JAMINAN MILIK PIHAK KETIGA DALAM PROSES KEPAILITAN - Prihartonoa, Eric; Yuhelson, Yuhelson; Franciska, Wira (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Curator in carrying out their duties, namely the settlement/sale of property bankruptcy conducted publicly in accordance with Article 185 UUK PKPU, but if the sale in public is not feasible, then the sale under the hand can be executed with the permission of the supervising judge. Procedures for the sale of bankruptcy property in specify in the legislation and other regulations such as Regulation of the Minister of Finance of the Republic of Indonesia number 213 / PMK.06/2020 about Implementation of the auction which was later amended through the regulation of the Minister of Finance of the Republic Indonesia number 122 of 2023 concerning auction implementation guidelines. One of the rules that changed regarding the sale of collateral objects on behalf of third parties in the process bankruptcy that causes ambiguity in the authority of the curator in carrying out their duties.